The complete guitar manual : the beginner's guide to playing the guitar - Sidwell, Jason (DK Publishing, 2020)
Whether you're a total novice about to buy your first guitar or you have already started playing and want to take your fretboard wizardry to the next level, The Complete Guitar Manual is the definitive fast-tract guide to becoming a guitar god. Learn how to play like the professionals with illustrated step-by-step sessions. Measure your progress along the way with specially written milestone pieces. Watch the online videos to learn how good technique looks and sounds, and play along with the backing tracks. Discover the inspiring listening recommendation of great guitarists of all styles. Choose and maintain your kit using the comprehensive equipment guide.